751 Preoperative Factors Influencing Functional Rehabilitation After Major Lower Limb Amputation. (4th May 2021) - Premnath, S; Cox, M; Hostalery, A; Kuhan, G; Rowlands, T; Quarmby, J; Singh, S
Abstract: Introduction: To identify the preoperative factors that influence functional rehabilitation after Major Lower Limb (MLL) amputation. Method: This retrospective study analyzed all patients referred post-amputation to an amputee rehabilitation centre over a period of 1 year. The level of functional outcome at 6 and 12 months were recorded using SIGAM (Special Interest Group in Amputee Medicine) grading. Data on various preoperative factors were collected and analyzed for association with functional outcome. Results: A total of 71 cases were analyzed. The mean age was 65.18 (range 24 - 91) years and 45 were males (63.4 %). Peripheral arterial disease was the major cause of amputation (80.3%). The level of amputation was above / through knee in 60.6%. Contralateral limb problems were present in 28.2%. Functional mobility was achieved by 38% of the MLL amputees within 6 months of rehabilitation, which increased to 46.5% at 12 months. Pre amputation mobility was a significant factor for a good functional outcome (p-value 0.002). An increasing value of BLARt (Blatchford Leicester Allman-Russell Tool) score showed a significant correlation with poor functional outcome. Conclusions: Pre amputation mobility and BLARt score can be used in the prediction of functional outcome and can aid in better pre-operative decision making and rehabilitation planning.